1968
DOI: 10.1017/s0043174500030423
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Annual Bluegrass and Turfgrasses to Bensulide and Three Uracil Herbicides

Abstract: Golf putting greens were sprayed with N-(2-mercaptoethyl) benzenesulfonamide S-(O,O-diisopropyl phosphorodithioate) (bensulide). Creeping bentgrass (Agrostis palustris Huds.) and annual bluegrass (Poa annua L.) were observed for injury. Preemergence and postemergence treatments of 5-bromo-3-sec-butyl-6-methyluracil (bromacil), 5-chloro-3-tert-butyl-6-methyluracil (terbacil), and 5-bromo-3-tert-butyl-6-methyluracil (hereinafter referred to as DP 733) were applied to a prepared seedbed planted with Kentucky blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1969
1969
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Some report excellent control of annual bluegrass with all of the PRE herbicides in their studies (6,7,11,15,17,18). Others report poor or erratic success with many of the same herbicides, rates, and method of application (2,7,12,14,24,25,29,33). In many of these studies bensulide was reported to control annual bluegrass very well (5,10,13,15,17,18,23,26,30,37), and in many of the same studies bensulide caused little or no injury to bentgrass (9,10,26,29,30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some report excellent control of annual bluegrass with all of the PRE herbicides in their studies (6,7,11,15,17,18). Others report poor or erratic success with many of the same herbicides, rates, and method of application (2,7,12,14,24,25,29,33). In many of these studies bensulide was reported to control annual bluegrass very well (5,10,13,15,17,18,23,26,30,37), and in many of the same studies bensulide caused little or no injury to bentgrass (9,10,26,29,30).…”
Section: Introductionmentioning
confidence: 99%
“…Others report poor or erratic success with many of the same herbicides, rates, and method of application (2,7,12,14,24,25,29,33). In many of these studies bensulide was reported to control annual bluegrass very well (5,10,13,15,17,18,23,26,30,37), and in many of the same studies bensulide caused little or no injury to bentgrass (9,10,26,29,30). However in these studies workers did not distinguish which subspecies of annual bluegrass was involved.…”
Section: Introductionmentioning
confidence: 99%
“…However, residual effects of DCPA on uniformity were slight; and little residual effect occurred from a single application. Neidlinger et al (4) reported that bensulide at 16.8 and 33.6 kg/ha did not cause visible injury to creeping bentgrass and colonial bentgrass (Agros tis tenuis Sibth) greens.…”
Section: Introductionmentioning
confidence: 99%
“…Herbicides normally used for preemergence crabgrass control in turf were reported to reduce the stand (2,3,5,7) and clipping weights of annual bluegrass (6). Bensulide (0,0-diisopropyl phosphorodithioate Sester with N-(2-mercaptoethyl)benzenesulfonamide) and DCPA (dimethyl tetrachloroterephthalate) gave control of annual bluegrass seeded immediately prior to treatment; however, when seeded at two months after treatment, no effect was noted.…”
Section: 4dditional Index Words: Bensulide Dcp a Plant Competitionmentioning
confidence: 99%